2019
DOI: 10.3390/s19235332
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Performance of Hybrid Rice Pot-Tray Sowing Utilizing Machine Vision and Machine Learning Approach

Abstract: Monitoring the performance of hybrid rice seeding is very important for the seedling production line to adjust the sowing amount of the seeding device. The objective of this paper was to develop a system for the real-time online monitoring of the performance of hybrid rice seeding based on embedded machine vision and machine learning technology. The embedded detection system captured images of pot trays that passed under the illuminant cabinet installed in the seedling production line. This paper proposed an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…By employing connected component detection, it calculates the number of seeds in each cell, providing valuable data for subsequent supplementary sowing. Dong Wenhao et al [5] developed a fixed threshold segmentation algorithm to differentiate grid images from seed images within seedling tray photographs. They also devised a technique to extract grid line pixel coordinates from grid images, which entails scanning contours within each image to inspect seed presence in cells, thereby calculating the number of misses and ultimately determining the missing rate of hybrid rice seeds.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…By employing connected component detection, it calculates the number of seeds in each cell, providing valuable data for subsequent supplementary sowing. Dong Wenhao et al [5] developed a fixed threshold segmentation algorithm to differentiate grid images from seed images within seedling tray photographs. They also devised a technique to extract grid line pixel coordinates from grid images, which entails scanning contours within each image to inspect seed presence in cells, thereby calculating the number of misses and ultimately determining the missing rate of hybrid rice seeds.…”
Section: Related Workmentioning
confidence: 99%
“…The detection accuracy of the number of seeds, ranging from zero to three particles in each single connected region, reached 95%, while the detection accuracy of the number of seeds exceeding four particles in each single connected region was up to 90%. Dong Wenhao et al [5] introduced a fixed As indicated in Figure 14, segmenting the eight types of images into 24 × 42 grids has improved the model's ability to detect missed sowing areas in seedling trays compared to the 16 × 28 grid parameter. The model successfully identified areas that were previously undetected under the 16 × 28 setting.…”
Section: Comparison With Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, several studies have been conducted on monitoring systems for automatically detecting these locations. Dong et al [13] developed a monitoring system capable of detecting missing rice seeds using machine vision and reached a detection accuracy of 94.67%. Bai et al [14] developed a monitoring system for corn seeds and improved the average detection accuracy to 97% by using RGB and hue saturation value (HSV) color space conversions.…”
Section: Introductionmentioning
confidence: 99%
“…The first group involves the use of appropriate software based on Visual Studio C ++ (Python, Java) and the OpenCV library (Li & He, 2017;The OpenCV Reference Manual, 2019;Wu et al, 2020) which can analyse all images obtained from a camera or by scanning. As a result of the analysis, the seeds are automatically identified by taking consecutive points around their perimeters and maximising or minimising the values in the following sequence: image loading; conversion to a 1-bit image (black seed on a white background); morphology analysis to remove noise and gaps; contouring by marking all the seeds in the image and calculating the length L, width B, area S and length of the perimeter P of the seed (Dong et al, 2019;Zhu et al, 2020). In this method, it is possible to place the seeds with a uniform distribution over the scan area and the ability to more clearly separate along the contours of its location The use of this method with the chaotic mixing of single-layer seed thickness consists of the formation of appropriate image preparation, its chromatic transformation and corresponding binarisation (Zilbergleit & Temruk, 2017;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%